A national survey of neonatal peripherally inserted central catheter (PICC) practices - Sharpe, Elizabeth; Pettit, Janet; Ellsbury, Dan L (Advances in neonatal care, 2013)
The purpose of this study was to assess and describe the practices involved in the insertion and maintenance of peripherally inserted central catheters (PICCs) in neonates in level III neonatal intensive care units (NICUs) in the United States and to compare the findings with current recommendations and evidence. The study included responses from 187 nurses, nurse practitioners, and neonatologists who place PICCs in NICUs representing 43 states. A 90-question, multiple-choice survey of a variety of PICC practices was sent to NICU directors and nursing staff responsible for PICC insertion. The explorative survey was sent by electronic and standard mail services. A descriptive analysis of the responses was performed. Main outcome measures included the response rate to the survey and the summarized responses of multiple categories of PICC practices. Of the 460 level III NICUs contacted, 187 returned surveys meeting criteria for analysis, yielding a 42% response rate. Responses showed wide variation of PICC practices in multiple aspects of PICC insertion and maintenance. The greatest level of conformity was seen with the following practices: use of 2 nurses to perform a dressing change, trimming the PICC, using a kit or cart containing insertion supplies, use of maximal sterile barrier precautions during insertion, catheter tip residing in the superior vena cava for upper body insertions, and not heparin locking, infusing blood products, performing catheter repair, or inserting using Modified Seldinger Technique. Some identified practices, such as infusion tubing change and catheter entry techniques, were contrary to current evidence and demonstrated a lack of correct information, and some represented safety concerns for the neonates having PICCs. This extensive national survey of NICU PICC practices showed wide variation in multiple aspects of PICC insertion and maintenance. A gap between the evidence and current practice was evident in many facets of training, insertion techniques, and maintenance processes. The data suggest a need for an increase in awareness of clinicians of current practice guidelines and standards and the need for further research to develop an evidence basis for many aspects of PICC care where lacking.